Global Positioning System (GPS) pada Kotak Penyimpanan Uang Berbasis Internet Of Things - Pratama, Aldo; Fitriani, Endah (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
In this research, a money storage box security system will be designed. The box designed is a box equipped with a vibration sensor and a GPS module, where vibrations due to lifting or if someone carries it triggers an alarm in the form of a buzzer that sounds and the control system is based on the NodeMCU ESP8266 which immediately sends a warning message and also a Google Maps link to the application. The most competitive Telegram is paid for by smartphone so it can be taken quickly to prevent it. Create a secure storage box based on Arduino Uno and Telegram and design a security system to find the location of the box via GPS with notification media via Telegram. The hardware used is an ultraisonic sensor to measure the height of the box from the floor, an IR Proximity sensor as an object detector, a fingerprint to open the box, a buzzer as an alarm, a solenoid lock to lock the box, GPS as a guide if the box is stolen, and an ESP8266 NodeMCU as an input process and output. By utilizing wifi from the NodeMCU ESP8266 as a link between the device and the cellphone.